The Safety and Efficacy of Tofacitinib in 24 Cases of Pediatric Rheumatic Diseases: Single Centre Experience - Kostik, Mikhail M.; Raupov, Rinat K.; Suspitsin, Evgeny N.; Isupova, Eugenia A.; Gaidar, Ekaterina V.; Gabrusskaya, Tatyana V.; Kaneva, Maria A.; Snegireva, Ludmila S.; Likhacheva, Tatyana S.; Miulkidzhan, Rimma S.; Kosmin, Artem V.; Tumakova, Anastasia V.; et al. (Frontiers in Pediatrics, 2022)
JAK-inhibitors are small molecules blocking the JAK-STAT pathway that have proven effective in the treatment of different immune-mediated diseases in adults and juvenile idiopathic arthritis (JIA). Aim of study: To evaluate the safety and efficacy of tofacitinib in children with different rheumatic diseases. Material and methods: We extracted information from 24 children with the following diagnosis: JIA (n=15), undifferentiated systemic autoinflammatory diseases (SAIDs) (n=7), and juvenile dermatomyositis (JDM) (n=2) who have been treated with tofacitinib for a period of longer than six months. The treatment outcomes were classified according to the opinion of the attending physicians as having a complete response (CR), i.e., the absence of disease activity, or a partial response (PR) – a significant improvement of symptoms and disease activity, or no response (NR) - no changes in disease activity. Results: CR was achieved in 10/24 patients; 7/15 among JIA patients, 1/2 among JDM patients, 4/7 among SAID patients, and PR in 5/15 of JIA, 1/2 of JDM, and 3/7 of SAID patients. Three non-responders with JIA discontinued tofacitinib. Corticosteroids were successfully tapered off in 11/14 patients and discontinued in 2/14 patients. Four patients had side effects not requiring treatment discontinuation: liver enzyme elevation (n=2), hypercholesterolemia (n=1), lymphadenitis (n=1). Conclusion: JAK-inhibitors are effective new therapies for the treatment of multiple immune-mediated diseases. Our experience has shown the best results in patients with JIA and JIA-associated alopecia, and type I interferonopathies. More data from randomized controlled clinical trials are needed to use JAK-inhibitors safely in pediatric rheumatic diseases.